The Trauma-Informed Approach to School Violence Interventions for Adolescent Learners with Physical Disabilities in Mainstream Schools - Shoko, Ratidzai (Indonesia Approach Education, 2024)
War, violence, disasters, sudden loss, serious illness, and other overwhelming and disturbing events constitute traumatic events. For learners with physical disabilities, trauma may result from the loss of function of a body part or previous exposure to violence. Attention is paid to the application of the trauma-informed approach in trying to curb school violence. This paper discusses the trauma-informed approach to school violence interventions for learners with physical disabilities. The article sought to explore the use of the trauma-informed approach to address school violence affecting learners with physical disabilities. The paper is built on the findings from my doctoral thesis on the effectiveness of interventions to control school violence in a special needs school. This paper uses secondary data sources such as journals and books as well as data from doctoral research. These will be discussed with the findings from the previous doctoral research. It was revealed that although there are policies put in place to address school safety, the rate of school violence is escalating. Against this background, there is a need to address school violence from a trauma-informed approach. The trauma-informed perspective will help to prevent violence and suggest interventions. It will also guide educators on how to support learners, victims, or perpetrators of school violence. By offering data based on research on the use of trauma-informed approaches as an alternative method of school violence intervention, this study contributes to the body of knowledge. It gives the stakeholders suggestions for how to care for and educate vulnerable children.